George Tyrrell and Catholic Modernism. Edited by Oliver P. Rafferty - Chapman, Mark D. (The journal of theological studies, 2011)
This book of eight essays addresses the life and thought of the Irish-born Catholic Modernist George Tyrrell. They were originally planned as papers for a conference that never happened to celebrate the hundredth anniversary of Tyrrell’s death as an excommunicate Jesuit in 1909. Although, as with most collections, there is much overlap between the essays, and there is inevitably a variation in depth, the overall standard is high. Most essays are far more substantial than conference papers and on unpublished sources as well as on Tyrrell’s substantial published output, much of it in relatively obscure places. Sometimes, as with the editor’s excellent discussion of Tyrrell’s relationship to the English Jesuits, there are some surprising details.